Management of Maxillofacial Gunshot Wounds: A Retrospective Study - Keyhan, Seied Omid; Mehriar, Peiman; Ghanean, Sina; Jahangirnia, Alireza (Regeneration, Reconstruction & Restoration (Triple R), 2016)
Introduction: Management of maxillofacial gunshot wounds (MGSWs) has long been challenging and a multidisciplinary approach in planning and reconstructing of MGSWs should be followed. The objective of this study was to retrospectively assess and present gunshot wound cases in a hospital in Iran. Materials and Methods: Fourteen MGSW at Departments of Oral and Maxillofacial Surgery at Jundishapur and Shahid Sadoughi Universities of Medical Sciences from 2011 to 2015 were retrospectively reviewed. Data was analyzed using SPSS version 16.0. Data was presented in the form of descriptive statistics: mean and standard deviation for all quantitative variables and frequency and percentages were presented for qualitative variables like gender, entry site of projectile, etc. Results: Age ranged from 18 to 42 years with mean of 27.34 years. There were 12 (85.7%) male and 2 (14.3%) female cases. From them, Ten (71.5%) patients required airway management. Mandible was the most frequent involved site (i.e, in 11 (78.5 %) patients), while midface was involved in 3 (21.5%) patients. Suicide was the main cause of gunshot (i.e, in 8 (57.1%) patients). Free fibular flap was applied in 4 (28.5%) patients, while 8 (57.1%) patients were managed with regional and distant flaps in combination with reduction internal fixation. The most common type of treatment was two stage delayed reconstruction (35.7%). Most of the patients (i.e, in 12 (85.7%) patients) had complications which trismus and infection were the most frequent complication being reported. Conclusion: This study shows that early management of MGSWs with local flaps results in better psychosocial profile, aesthetics, reduced hospital stay and faster functional rehabilitation.